Fortalecimiento de la Identidad Cultural del Cacao para el Desarrollo Turístico del Cantón Palanda, Provincia Zamora Chinchipe - Merino Luzuriaga, Rhinela Dayana (2023)
This research project is aimed at the rescue and recovery of the cultural identity of cocoa, originally from the Palanda canton, Zamora Chinchipe province, its origin can be evidenced from the vestiges found by the assents of the Mayo Chinchipe culture in the sector Santa Ana Florida. The research project "Strengthening the Cultural Identity of Cocoa for the Tourist Development of the Palanda Canton, Zamora Chinchipe Province", has the general objective of strengthening the tourist development of the Palanda canton, through the cultural identity of cocoa, supporting the rescue of the cultural identity of cocoa and contributing to the cultural, social, economic and tourist development of the place, offering tourists an innovative and quality product. For the elaboration of the research work, it was necessary to propose three specific objectives: Diagnose the origin, uses and manifestations of cocoa for the tourist development of the Palanda canton, where a situational diagnosis of cocoa was made in the Palanda canton, INPC sheets were applied and Mintur for the collection of information, online, physical surveys and interviews were applied, taking into account the economically active population, a crossed and strategic SWOT of the results obtained was carried out, a second objective was developed, Make a proposal for the strengthening cocoa tourism in the Palanda canton, from the strategies obtained from the diagnosis, the proposal was developed, applying the methodology of Marvin Blanco (2008), which consists of 3 phases, a third objective was given, to establish a tourism development model in the Palanda canton based on the cultural identity of cocoa, a model in which a training and talks program was developed, which was established as a proposal in the previous objective. When carrying out the analysis of results, it was determined that the population has great interest in cocoa, which is why it was determined to carry out training to improve the production and manufacture of cocoa-based products. Finally, some conclusions were established by objectives where it is mentioned that cocoa has potential for the development of the Palanda canton, in addition recommendations are described for the authorities, entrepreneurs and for the National University of Loja.